On linear isometries on non-archimedean powerseries spaces - Śliwa, Wiesław; Ziemkowska, Agnieszka (My University, 2012)
The non-archimedean power series spaces Ap(a; t) are the most known and important examples of non-archimedean nuclear Frechet spaces. We study when the spaces Ap(a; t) and Aq(b; s) are isometrically isomorphic. Next we determine all linear isometries on the space Ap(a; t) and show that all these maps are surjective.
Keywords: non-archimedean power series space; linear isometry; Schauder basis